Multiple criteria selection of pile-column construction technology - Zavadskas, Edmundas Kazimieras; Sušinskas, Saulius; Daniūnas, Alfonsas; Turskis, Zenonas; Sivilevičius, Henrikas (Journal of Civil Engineering and Management, 2012)
Numerous alternatives exist for foundation systems and construction technologies. The systems can be described by different criteria values which are incorporated in the conventional design process. Decision on the most suitable construction technology is vital for success and depends on many effectiveness criteria. The business success depends on the right choice. The mandate of a construction management researcher is to use rational, systematic, science-based techniques to inform and improve various decisions. The paper presents multiple criteria decision making model for selection of a pile-column technology. The technological criteria are determined by an experimental study. Based on in-situ investigation of natural soil conditions, criteria values are determined. The decision making model incorporates five different methods and techniques. To solve a problem, it uses three multiple criteria decision making methods. Integrated criteria weights are determined by using the analytic hierarchy process and the expert judgement method. This model could be used to solve complicated problems pertaining to the selection of a construction technology.